ANALISIS PENERAPAN PROFIL PELAJAR PANCASILA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SD NEGERI 73/IV KOTA JAMBI - Wahyu Oktavianto, Andry; Widayanti, Evika; Masturoh, Masturoh; Winda, Nirmala; Eka Putri, Prili; Sofwan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to identify the strategies used by teachers in implementing the Pancasila Student Profile to shape students' character. The research was conducted at SD Negeri 73/IV Kota Jambi using a descriptive qualitative method, which describes the implementation of the Pancasila Student Profile and the strategies used by teachers to realize it. The research subjects were 19 fourth-grade students. Data collection was carried out through observation and interviews. The observation results showed that teachers used strategies such as differentiated learning, project-based learning, and habituation. The study indicates that teachers have successfully implemented these strategies, as evidenced by improved student grades. Teacher creativity in designing learning activities is key to the success of implementing these strategies. In addition to teachers, the roles of family and social environment are also important in shaping students' character.